2018
DOI: 10.12691/ajrd-6-1-3
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Access to ICT Based Media in Receiving Farm Information: A Grassroots Level Study from Bangladesh

Abstract: Information is one of the vital factors of production while ICT to provide efficient and effective information. Thus, the study was undertaken mainly to determine farmers' extent of access to ICT based media in receiving agricultural information. Besides, important factors associated with farmers' extent of access to ICT based media were also explored. The study was conducted at Fulbaria upazila (sub-district) under Mymensingh district in Bangladesh. Eighty (80) farmers were interviewed using structured questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 5 publications
5
11
1
Order By: Relevance
“…This conforms to the results of Oladele et al (2018). Availability of ICT tools has also been reported to enhance information access through ICT in Bangladesh (Khalak et al, 2018). The negative relationship between ownership of radio and extension pathway could be due to the complementarity of the two pathways.…”
Section: Discussionsupporting
confidence: 87%
“…This conforms to the results of Oladele et al (2018). Availability of ICT tools has also been reported to enhance information access through ICT in Bangladesh (Khalak et al, 2018). The negative relationship between ownership of radio and extension pathway could be due to the complementarity of the two pathways.…”
Section: Discussionsupporting
confidence: 87%
“…Khalak et al [22] carried out an investigation to find out farmers' access to different ICT based media for getting agricultural information. Findings (Table 5)…”
Section: Ingression To Different Ict Based Mediamentioning
confidence: 99%
“…A focus group discussion (FGD) was conducted by [22] to elucidate the problems faced by the farmers in receiving agricultural information using ICT based medias. It was observed that ( [23] majority (61.25%) of the farmers mentioned that poor level of their education is the highest-level problem for getting better access to ICT based media.…”
Section: Troubles In Getting Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chowhan & Ghosh (2020) conducted a study on the role of ICT in agriculture and its future scope in Bangladesh and found that farmers and extension staff have limited access, level of knowledge and capacity to use ICTs. Another study conducted by Khalak et al, (2018) on farmers' access to ICT-based media in receiving information and reported that the majority of the farmers had low access to ICT-based media in receiving farm information. Syiem & Raj (2015) accomplished a study on access and usage of ICTs by the tribal farmers in Meghalaya State of North-East India.…”
Section: Introductionmentioning
confidence: 99%